Existence Test Of Escherichia Coli and Pseudomonas Aeruginosa Bacteria in Packaging Drinking Water in Cemani Village, Sukoharjo Regency - Nuraini Putri Rahmawati; Wardani Siska Tatiana; Veranita Weri (Proceeding of International Conference on Science, Health, And Technology, 2021)
Clean, potable fresh water is becoming scarce in cities, the river which is the source of it is polluted with various wastes ranging from organic waste, household waste, to industrial waste. The quality of drinking water also affects public health, especially bottled drinking water. One of the parameters for the quality requirements of bottled drinking water is the test for Escherechia coli and Pseudomonas aeruginosa bacteria. The purpose of this study was to identify the contamination of Escherechia coli and Pseudomonas aeruginosa bacteria in bottled drinking water samples, using the MPN (Most Probable Number) method. The research method uses descriptive research. The research population of bottled drinking water in stalls around the Duta Bangsa University Surakarta campus is as many as 7 samples. Collecting data by laboratory observation, data analysis with descriptive analysis. The results of the study were carried out from seven samples of bottled drinking water, all samples were not detected by the Escherechia coli and Pseudomonas aeruginosa bacteria. The conclusion of this study is that there are no Escherechia coli and Pseudomonas aeruginosa bacteria in bottled drinking water sold in stalls around the campus of Universitas Duta Bangsa Surakarta.